The risk of concomitant injuries of the contralateral side in valgus injured knee by lateral bumper impact – "Windswept injury mechanism"-. Issue 8 (August 2020) - Sim, Jae Ang; Na, Young Gon; Lee, Dong Whan; Kwon, Hyuk Min; Lee, Byung Hoon
Highlights: Understanding of injury mechanism with consideration to knee position and forces can provide to accurate assessment of the extent of knee injuries. By "Windswept injury mechanism ", concomitant major ligament injuries in the contralateral knee can be developed with the risk of ACL injury. Sequential knee abduction load and trunk motion by lateral bumper impact is the risky injury mechanism in the contralateral knee. Abstract: Purpose: Valgus injury of high energy of the lateral bumper impact can lead blows to the inside of the knee that push the knee outwards or indirect injury where a varus force is applied to the contralateral knee, which injury pattern named as " Windswept injury mechanism " in this study. The objective of this study was to establish injury pattern in the contralateral side knee on the basis of this pattern recognition to enhance a diagnosis of interrelated osseous and soft-tissue injuries. Methods: Sixteen patients by " Windswept injury mechanism " were identified, who visited a level 1 trauma center between Jan 2007 and Dec 2016. We first evaluated the osseous and soft tissue injuries at primary impacted site by valgus force after checking MRI. Thereby, assessed the contralateral knee which structures were injured. To find any correlation between both knees in ligament injuries, patients were divided into two groups according to coincided anterior cruciate ligament (ACL) rupture. Results: By the " Windswept injury mechanism ", MCL total rupture was observed in all primary knees, and the major ligament injuries also were coincided on the contralateral knee. In primary knee, either ACL or PCL was ruptured in all cases. 9 patients (56%) had combined ACL rupture with MCL injury, 12 patients (75%) of combined PCL injury, and 5 patients (31%) had combined injury of both ACL and PCL. In contralateral knee, lateral collateral ligament injury was observed in 69%. 7 patients (44%) was combined with ACL injury, 7 patients (44%) with combined PCL injury, 4 patients (25%) with combined both ACL and PCL injury. In comparison of two groups, significantly higher risk of ACL injury in the contralateral knee was identified when coincided ACL and MCL injury in primary knee ( p  = 0.003). Conclusion: The specific mechanism-based injury pattern of "Windswept injury mechanism " was the first to identify the mechanism that showed concomitant major ligament injuries in the contralateral knee and to develop validated the higher risk of ACL injury in the contralateral knee when combined ACL and MCL injuries in primary knee, which improving diagnosis of potentially subtle and easily missed knee injuries.